Validation of the manufacturing process used to produce long‐acting recombinant factor IX Fc fusion protein. (8th May 2014) - McCue, J.; Osborne, D.; Dumont, J.; Peters, R.; Mei, B.; Pierce, G. F.; Kobayashi, K.; Euwart, D.
Summary Recombinant factor IX Fc (rFIXFc) fusion protein is the first of a new class of bioengineered long‐acting factors approved for the treatment and prevention of bleeding episodes in haemophilia B. The aim of this work was to describe the manufacturing process for rFIXFc, to assess product quality and to evaluate the capacity of the process to remove impurities and viruses. This manufacturing process utilized a transferable and scalable platform approach established for therapeutic antibody manufacturing and adapted for production of the rFIXFc molecule. rFIXFc was produced using a process free of human‐ and animal‐derived raw materials and a host cell line derived from human embryonic kidney (HEK) 293H cells. The process employed multi‐step purification and viral clearance processing, including use of a protein A affinity capture chromatography step, which binds to the Fc portion of the rFIXFc molecule with high affinity and specificity, and a 15 nm pore size virus removal nanofilter. Process validation studies were performed to evaluate identity, purity, activity and safety. The manufacturing process produced rFIXFc with consistent product quality and high purity. Impurity clearance validation studies demonstrated robust and reproducible removal of process‐related impurities and adventitious viruses. The rFIXFc manufacturing process produces a highly pure product, free of non‐human glycan structures. Validation studies demonstrate that this product is produced with consistent quality and purity. In addition, the scalability and transferability of this process are key attributes to ensure consistent and continuous supply of rFIXFc.